#### Answer

14,41

#### Work Step by Step

Let the smaller number be $x$ and the larger number be $y$.
Since the difference of the two numbers is 27, we obtain:
$y-x=27$
When three times the smaller number is subtracted
from the larger number, the result is -1, so we write
$y-3x=-1$
$y=3x-1$
Therefore, we now have a pair of equations to solve. Substituting the second equation into the first equation, we obtain:
$y-x=27$
$3x-1-x=27$
$2x-1=27$
$2x=27+1$
$2x=28$
$x=14$
Substituting the value of $x$ in the first equation to find the value of $y$, we obtain:
$y-x=27$
$y-14=27$
$y=27+14$
$y=41$
Therefore, the smaller number is 14 while the larger number is 41.